2015
DOI: 10.1002/hep.27745
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepatic resection in the treatment of hepatocellular cancer

Abstract: Current guidelines recommend surgical resection as the primary treatment for a single hepatocellular cancer (HCC) with Child's A cirrhosis, normal serum bilirubin, and no clinically significant portal hypertension. We determined how frequently guidelines were followed and whether straying from them impacted survival. BRIDGE is a multiregional cohort study including HCC patients diagnosed between January 1, 2005 and June 30, 2011. A total of 8,656 patients from 20 sites were classified into four groups: (A) 718… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
286
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(331 citation statements)
references
References 25 publications
10
286
0
13
Order By: Relevance
“…(1) The authors raise the important issue of primary mouse hepatocyte (PMH) dedifferentiation in culture. We considered this and looked for RIPK3 in "freshly isolated PMH" multiple times in phosphate-buffered saline-treated mice and mice treated with acetaminophen (APAP) for 3 hours.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The authors raise the important issue of primary mouse hepatocyte (PMH) dedifferentiation in culture. We considered this and looked for RIPK3 in "freshly isolated PMH" multiple times in phosphate-buffered saline-treated mice and mice treated with acetaminophen (APAP) for 3 hours.…”
Section: Replymentioning
confidence: 99%
“…We read with interest the article by Roayaie et al (1) regarding the surgical management of hepatocellular carcinoma (HCC) within the Bridge database. As reported by the authors, about two-thirds of resected patients were not ideal candidates for surgery according to published guidelines; in particular, 37% had portal hypertension (PH), and 7% were Child-Pugh B-C.…”
Section: To the Editormentioning
confidence: 99%
“…This conclusion was based on an international multicenter study by Roayaie et al, (1) which reported a 5-year overall survival rate of >30% in the suboptimal group. This group of patients accounted for nearly 70% of all the patients who underwent hepatic resection during the study period.…”
mentioning
confidence: 95%
“…Although the current European and American guidelines for HCC do not recommend hepatic resection for patients with intermediate or advanced HCCs, with Child B liver function, or concurrent portal hypertension, many hepatic surgeons around the world still operate on such patients on a selective basis provided the perioperative mortality and morbidity rates are estimated to be low. (1)(2)(3) In real life, a significant proportion of these patients would also choose surgical resection because of the potential cure despite a high tumor recurrence rate after resection.…”
mentioning
confidence: 99%
“…Surgical resection is the favored option for advanced HCC before any other treatment option [4]. However, options that delay tumor progression in the absence of a major tumor burden reduction such as treatment with sorafenib [5] or regorafenib [6] are seen as less appealing even if survival -the most valued endpoint -may be similar or even better.…”
mentioning
confidence: 99%